Peningkatan Kemampuan Berpikir Kritis Tema Peristiwa dalam Kehidupan Melalui Model Kooperatif Think Pair Share Kelas VA SDN Giwangan - Isnanda Ariztasari (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This research aims at improving the process of learning and improving the critical thinking skill using cooperative learning model type of think pair share at social studies for grade VA student SDN Giwangan. This research was classroom action research which refered to spiral model from Kemmis and Taggart. Data was collected by test and observation. The analize of data used descriptive quantitative. The result shows that cooperative learning type think pair share on social studies can improve the critical thinking skill. This is showed by average scores and mastery learning percentage in pre action, cycle 1, and cycle II. In pre action, average score is 54,81 and mastery learning percentage is 25%. In cycle 1, average score increase to 75,64 and mastery learning percentage increase to 61%. In cycle II, average score increase to 81,61 and mastery learning percentage increase to 77%.